2023
DOI: 10.1039/d2ra08180f
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning based implicit solvent model for aqueous-solution alanine dipeptide molecular dynamics simulations

Abstract: Here we investigated the use of machine learning (ML) techniques to “derive” an implicit solvent model based on the average solvent environment configurations from explicit solvent molecular dynamics (MD) simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 129 publications
0
4
0
Order By: Relevance
“…Our conclusions on the importance of multibody terms are consistent with the findings of Wang et al, who, by using a bottom-up approach, showed that multibody terms are needed for small proteins to reproduce the folding free energy landscape of atomistic simulations correctly. For this reason and to allow a more expressive functional form for the multibody terms, recent advances in the development of protein CG models make use of neural networks to represent nonbonded interaction potentials. , …”
Section: Discussionmentioning
confidence: 99%
“…Our conclusions on the importance of multibody terms are consistent with the findings of Wang et al, who, by using a bottom-up approach, showed that multibody terms are needed for small proteins to reproduce the folding free energy landscape of atomistic simulations correctly. For this reason and to allow a more expressive functional form for the multibody terms, recent advances in the development of protein CG models make use of neural networks to represent nonbonded interaction potentials. , …”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, one can adopt an implicit description of the MM environment through the use of MM‐perturbed semi‐empirical QM charges, 82,83 MM electrostatic potential or field at QM atom positions, 84,85 or through polarizable embedding 86 . One can also use both MM electrostatic potential and field in the training of QM/MM MLPs 81,87 using our QM/MM‐AC scheme 80 for separating inner and outer MM atoms and projecting outer MM charges onto inner MM atom positions 80,88,89 …”
Section: Discussionmentioning
confidence: 99%
“…A classic example is the alanine dipeptidea small, thoroughly studied system where a biomolecule exhibits rare events in solution at room temperature. It is typically used for benchmarking various enhanced sampling methods and lately, the quality of machine learning potentials. , Therefore, generating more reference (“training”) data is essential for the development and validation of novel force field parameters. The ever-increasing computational power, including promising advances in quantum computing, is anticipated to become increasingly important in producing such data, e.g., through accelerated and AI-enhanced first-principles calculations.…”
Section: Coupling Molecular Dynamics and Artificial Intelligencementioning
confidence: 99%